Construction of boric acid‐functionalized metal–organic frameworks for glycopeptide recognition in the serum of cervical cancer patients - Rao, Dongping; Wang, Baichun; Zhong, Huizhen; Yan, Yinghua; Ding, Chuan‐Fan (Rapid communications in mass spectrometry, 2022)
Rationale Cervical cancer is one of the most common malignant tumors in women, and it is essential to explore potential biomarkers such as glycopeptides closely related to cancer in physiological samples of cervical cancer patients. Sample pretreatment is required before direct detection using mass spectrometry because there are certain limitations. Meanwhile, it is still highly desired to promote the functionalization and application of metal–organic framework (MOF)‐derived materials. Methods Using a post‐synthesis modification method, a novel type of boric acid‐functionalized MOF probe (designated as UiO‐66@PEI@Au@B(OH)2) is prepared for recognition of glycopeptides. The results are obtained using matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry and nano‐liquid chromarography–tandem mass spectrometry. Results The UiO‐66@PEI@Au@B(OH)2 probe exhibits a low detection limit (0.6 fmol μL−1), an excellent recovery rate, comparatively good reusability and selectivity (HRP digests:BSA digests = 1:500). When UiO‐66@PEI@Au@B(OH)2 is used to selectively capture glycopeptides from the serum of a healthy person and a cervical cancer patient, 101 glycopeptides corresponding to 54 glycoproteins and 108 glycopeptides corresponding to 57 glycoproteins are detected, respectively. Conclusions The successful preparation of UiO‐66@PEI@Au@B(OH)2 provides a path for the investigation of the functionalization of MOF‐derived materials. The excellent performance of UiO‐66@PEI@Au@B(OH)2 not only demonstrates the huge potential of functionalized MOFs in the glycoproteome, but also opens up new phases of the application of MOF‐based materials.